The effect of initial strength of concrete wastes on the fresh and hardened properties of recycled concrete reinforced with recycled steel fibers. (20th September 2021) - Sahraei Moghadam, Amirhosein; Omidinasab, Fereydoon; Abdalikia, Mehdi
Highlights: The initial strength of RCAs was recognized as one of the influential parameters in the behavior of recycled concrete. RSF significantly enhanced the tensile and flexural strength of recycled concrete. Multi-criteria optimization results justified the use of 50% high initial strength RCAs as well as RSF. Abstract: The initial strength of concrete wastes is one of the most influential parameters in the behavior of recycled concrete. In this paper, in the production of recycled concrete aggregates (RCA), three types of concrete wastes with initial strength of 20, 40, and 80 MPa were used. Natural aggregates (NA) were replaced by RCAs with amounts of 0, 50, and 100% by volume. In addition, the specimens were reinforced with 0, 0.5, and 1% by volume of recycled steel fibers from scrap tires (RSF). Workability, water absorption, ultrasonic pulse velocity (UPV), mechanical properties (compressive strength, splitting tensile strength, and flexural strength) as well as economic aspects of 21 mixtures were assessed. The results showed that the use of RCAs have a negative effect on the workability, quality, and mechanical properties of concrete, which can be prevented by increasing the initial strength of RCAs and also using RSF. Finally, multi-criteria optimization (MCO) indicated that the use of RSF and 50% RCAs with initial strength of 40 and 80 MPa is justified, in terms of workability, quality, water absorption, mechanical properties, and economic aspects.